Histamine-Induced Conjunctivitis and Breakdown of Blood–Tear Barrier in Dogs: A Model for Ocular Pharmacology and Therapeutics - Sebbag, Lionel; Allbaugh, Rachel A.; Weaver, Amanda; Seo, Yeon-Jung; Mochel, Jonathan P. (Frontiers in Pharmacology, 2019)
Conjunctival inflammation disturbs the blood-tear barrier and thus affects the tear film stability and composition. We aimed to develop a non-invasive and reliable method to induce conjunctivitis in dogs, a large animal model for translational work on ocular surface disease in humans. Six beagle dogs underwent a randomized, vehicle-controlled, balanced crossover trial – on six separate days, one eye received topical artificial tears (vehicle) while the other eye received 1 of 6 concentrations of histamine solution (0.005 to 500 mg/mL). At sequential times after eyedrop administration, a conjunctivitis score was given to each eye based on the degree of palpebral and bulbar conjunctival hyperemia and chemosis, ocular pruritus and discharge. Total protein content (TPC) and serum albumin were quantified in tear fluid at baseline and 20 min. Additionally, 13 dogs presenting for various ophthalmic diseases with associated conjunctivitis were examined. Experimentally-induced conjunctivitis developed rapidly (< 1 min) following topical histamine administration and lasted for 1-3 h (4 lowest doses) to 6-8 h (2 highest doses). The severity of conjunctivitis was dose-dependent. Histamine was overall well tolerated, although transient blepharitis, aqueous flare and ocular hypertension occurred in a few dogs receiving histamine ≥ 375 mg/mL. TPC and serum albumin levels increased in tears of eyes receiving histamine ≥ 1.0 mg/mL, being significantly higher than placebo and baseline in eyes receiving histamine ≥ 375 mg/mL. Lacrimal albumin levels were also increased in 13 dogs with naturally-acquired conjunctivitis, up 2.7-14.9 fold compared to contralateral healthy eyes. Histamine-induced conjunctivitis represents a robust model for translational work on the ocular surface given the low cost, non-invasiveness, self-resolving nature, ability to adjust the duration and severity of the disease, and shared features with naturally occurring ocular diseases. Histamine solutions of 1, 10 and 375 mg/mL induce mild, moderate and severe conjunctivitis in dogs, respectively. Leakage of serum albumin in tear fluid of eyes with conjunctivitis suggests a breakdown of the blood-tear barrier.